Traffic impact analysis on Paris and suburbs ways using BFSIS model. (2017) - Uzunova, Milka; Velichkova, Rositsa; Potarusov, Roman; Darcherif, Moumen A.
In current paper are presented an original approach which is deal with the analysis of the traffic flow density and the travel time as additional indicators using a new extension of the well-known breadth-first search (BFS) algorithm. The average road grade and the average legal speed on the road as well as weather conditions are taken into account. Addition to these indicators, this paper is focused on the road traffic measurement as a supplementary parameter required when calculating the electric vehicle energy consumption.